Characterization of Physical, Chemical and Functional Properties of Flour of Locally Grown Wheat - Murtini, Erni Sofia; Susanto, Tri; Kusumawardani, Ratih (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
It was reported that a group of experts in 2000 had successfully adapted some Indian wheat varieties in Indonesia. After a series of trial in 15 Provinces, they claimed that some varieties showed promising yields, up to 3,5 ton per hectare, a level that was definitely higher than those yielded in its original habitat. Despite the success, there has not been a report on characteristic of its flour. The study was therefore conducted to evaluate physical and chemical properties as well as its functional properties of the flour processed from there locally grown Indian wheat varieties so called Dewata, Selayar and Nias, and to compare them to those of known wheat varieties i.e. Australian Hard Wheat (AHW) and Australian Standard Wheat (ASW) The properties assessed include the weight per 1000 of seeds, proximate composition, and some rheological properties, and were carried out on a group of samples taken randomly. The data were then analyzed by means of Analysis of Variance and subsequently followed by Duncanâ€™s Multiple Range Test to see if any difference amongst the varieties. The results showed that Nias wheat variety has a comparable weight of seed than that of AHW and ASW, while the ones of Selayar and Dewata are somewhat higher. Based on the protein content, Dewata which contains 11,63% protein may be classified as a high protein group of wheat, similar to AHW (11% protein), while the other two varieties containing about 10% protein fall into a medium-level protein group. The ASW varieties belongs to low protein wheat since it contains only 8,44% protein. However, the farinograph, extensograph and alveograph test indicated that the flour of the locally grown wheat possesses a less desirable gluten quality. Â Key Words: locally grown wheat variety, characterization